Inspiratory muscle dysfunction and restrictive lung function impairment in congenital heart disease: Association with immune inflammatory response and exercise intolerance. (1st November 2020) - Spiesshoefer, Jens; Orwat, Stefan; Henke, Carolin; Kabitz, Hans-Joachim; Katsianos, Stratis; Borrelli, Chiara; Baumgartner, Helmut; Nofer, Jerzy-Roch; Spieker, Maximilian; Bengel, Philipp; Giannoni, Alberto; Dreher, Michael; et al.
Abstract: Background: In adult patients with congenital heart disease (ACHD), both underlying disease and lung restriction contribute to exercise intolerance. In ACHD the yet incompletely understood mechanism underlying restricted ventilation may be inspiratory muscle weakness. Therefore, this study comprehensively evaluated inspiratory muscle function in ACHD and associations with systemic inflammation and the clinical severity of exercise intolerance. Methods: 30 ACHD patients (21 men, 35 ± 12 years) and 30 healthy controls matched for age, gender and body mass index underwent spirometry, measurement of mouth occlusion pressures, and diaphragm ultrasound. Six-minute walking distance (6MWD) and New York Heart Association functional class were used to quantify exercise intolerance. Interleukin-6 (IL-6) and tumor necrosis factor-alpha (TNF-α) levels were measured using enzyme-linked immunosorbent assays. Results: ACHD patients showed lower forced vital capacity (FVC), and maximum inspiratory (PImax) and expiratory (PEmax) pressures compared with controls (all p < 0.05). On ultrasound, ACHD patients showed a lower diaphragm thickening ratio (2.3 ± 0.5 vs. 2.8 ± 0.9, p < 0.01) and lower diaphragm excursion velocity during a voluntary sniff maneuver (5.7 ± 2.2 vs. 7.6 ± 2.0 cm/s, p < 0.01). Respiratory parameters, such as FVC (r = 0.53; p < 0.01) and PImax (r = 0.43; p = 0.02), correlated with 6MWD. Furthermore, amino terminal pro B-type natriuretic peptide levels were inversely correlated with FVC (r = −0.54; p < 0.01). Circulating pro-inflammatory cytokines were markedly increased, and IL-6 was correlated with 6MWD, dyspnea, and biomarkers of heart, lung and inspiratory muscle function (all p < 0.05). Conclusions: Our findings show that diaphragm dysfunction is present in ACHD and relates to restrictive ventilation disorder and exercise intolerance, possibly mediated by increased IL-6 levels. Highlights: Adult patients with congenital heart disease (ACHD) show diaphragm dysfunction. Inspiratory muscle dysfunction in ACHD is associated with exercise intolerance. Dyspnea is correlated with inspiratory muscle dysfunction in ACHD. Inspiratory muscle dysfunction in ACHD may be linked to systemic inflammation.